3-D SEISMIC TOMOGRAPHY VP AND VP/VS RATIO BENEATH NORTHERN SUMATRA REGION USING DATA CATALOGS OF MCGA AND PASSCAL NETWORKS - JATNIKA (NIM : 22411308); Pembimbing : Dr. Andri Dian Nugraha, M.Si.; Dr. Wandono, JAJAT
We have determined the structure of P-wave velocity, S-wave velocity and Vp/Vs ratio beneath the Northern Sumatra region. The data used in this study compiled by MCGA (from 2009 to 2012) and adjoining the catalog of PASSCAL (February to May 1995). In total, there are 2,246 local earthquake events with 10,666 Pwave phases and 6,257 S-wave phases from 62 stations seismic around the study area. Ray tracing to estimate travel time from source to receiver in this study by applying pseudo-bending method while the damped LSQR method was used for tomography inversion. Based on assessment of ray coverage, earthquakes dan stations distribution, we set up horizontal grid nodes of 30x30 km2 inside the study area and 80x80 km2 for outside the study area. In this study we have conducted inversions simultaneously with local earthquakes relocation. More than 60% events of fixed depth (10 km) can relocate by use of 3D velocity structure. The relocation result disclose the distribution of shallow earthquakes in mainland more tight and coincide with the fault zone. While our tomographic inversion results show low Vp and low Vs anomalies beneath the Toba caldera complex region and around the Sumatra Fault Zones (SFZ). These features are consistent with previous study. The interesting phenomenons of strong low Vp and low Vs are exhibit at depths of about 20 km which are may be related to volcanic front line in the northern part of Sumatra region. The low Vp, low Vs, and high Vp/Vs ratio value are also observed beneath Toba caldera complex especially around Mt. PusuBukit at depths of 5 km down to 100 km. Our interpetation about these anomalies may be related to ascending hot materials from subduction processes at depths of 80 km down to 100 km. Slab subduction beneath northern Sumatra (although not very clear) indicated with high perturbations P wave and S wave velocity. The obatained seismic velocities from local tomography will give valuable information for enhance our understanding of tectonic and volcanic in this study area.